Viral Transmission in Sea Food Systems: Strategies for Control and Emerging Challenges - Dingsong Lin; Wendi Chen; Zejia Lin; Lingdai Liu; Molan Zhang; Hongshun Yang; Zifei Liu; Lin Chen (Foods)
The SARS-CoV-2 pandemic had widespread and severe impacts on both the global economy and human health. Facing the continuously mutating virus, this crisis has heightened concerns among consumers and businesses regarding viral transmission through seafood, particularly in the face of emerging, unknown viruses, underscoring our preparedness gaps. This review provides a succinct overview of the survival mechanisms of prevalent viruses in seafood, examines potential transmission pathways to humans during seafood processing, and discusses strategies for mitigating their spread throughout the seafood supply chain. Furthermore, the discussion highlights emerging trends in innovative antiviral technologies aimed at enhancing food safety. Person-to-person transmission remains the most likely source of infection within the supply chain. Therefore, it is still imperative to adhere to the implementation of standard processes, namely good manufacturing practices (GMP) and good hygiene practices (GHP), in the seafood business. In light of the significant losses caused by this crisis and the persistent presence of various viruses within the seafood supply chain, efforts are needed to implement predictive and preventive measures against potential emerging viruses. Future research should focus on monitoring and limiting viral transmission by integrating Industry 4.0 applications, smart technologies, and antiviral packaging, maximizing the potential of these emerging solutions.